Empowering Coastal Women through Local Food Innovation and Financial Digitalization to Support Sustainable Marine Tourism - Yunita Ningsih Christiani; Mesri Welhelmina Nisriani Manafe; Gabriela Hetharia; Marce Serly Kase; Herny Constantia Fanggidae (LP2M INSURI Ponorogo, 2026)
Community-based tourism has become a strategic approach to promoting sustainable coastal development while improving local communities' welfare. This community service program aims to strengthen the economic capacity of coastal women by improving entrepreneurial skills, increasing business income, and enhancing the adoption of digital financial applications through an integrated approach combining local food innovation, financial literacy, and digital financial management to support sustainable marine tourism development in Kupang City. The program was implemented in Pantai Warna, Oesapa Village, involving 10 coastal women micro-entrepreneurs managing local culinary businesses. The activities were conducted over 6 months using a participatory empowerment approach, including problem identification, training in local food product innovation and financial literacy, assistance with digital financial applications, and monitoring and evaluation. This program differs from previous initiatives by integrating local food innovation, digital financial literacy, and strengthening the tourism ecosystem into a single empowerment model.